Feeding the Megacity: Challenges to Achieve Food Security in Jakarta - Fiisabilillah, Dika Fajri; Maulana, Alvaryan (Journal of Regional and City Planning, 2016)
Food security has nowadays become a major challenge for many countries including Indonesia, which has included it in its Food Law. Meanwhile, urban transition entails massive land conversion from non-built (agriculture) to built environment. This transition makes the lawâs objectives more difficult to achieve and consequently adds to the complexities of metropolitan governance and planning. Using Jakarta as a case study, this article aims to describe the condition of Jakartaâs food security, being the only megacity in Indonesia. This research uses a mixed method approach with content analysis and descriptive statistical analysis. The analysis investigates the components of food security, which include availability, accessibility, utilization, and stability. The research found that each component has faced particular problems that are mutually connected, and the local government has yet to recognize the urgency of this issue. This research stresses the urgency of local governmentâs role and the need for strong and sustainable cooperation with other regions, particularly Jakartaâs peri-urban region, in managing Jakartaâs food system.Keywords. Urban food security, megacity, JakartaÂ Ketahanan pangan telah menjadi tantangan utama bagi berbagai negara termasuk Indonesia, yang telah memasukkannya ke dalam undang-undang pangan. Pada sisi lain, perkembangan perkotaan telah menyebabkan alih fungsi lahan secara besar-besaran dari pertanian menjadi kawasan terbangun. Transisi ini menyebabkan tujuan undang-undang menjadi sulit untuk dicapai dan meningkatkan kompleksitas tata kelola kawasan metropolitan. Artikel ini bertujuan untuk menggambarkan kondisi ketahanan pangan Jakarta, sebagai satu-satunya megapolitan di Indonesia. Penelitian ini menggunakan pendekatan campuran khususnya metode analisis isi dan statistik deskriptif. Analisis mengidentifikasi komponen-komponen ketahanan pangan, termasuk ketersediaan, aksesibilitas, penggunaan, dan stabilitas. Penelitian ini menunjukkan bahwa setiap komponen menghadapi masalah tersendiri yang saling terkait, dan pemerintah daerah masih harus menemukan urgensi permasalahannya. Penelitian ini menekankan pentingnya kerja sama yang kuat dan berkelanjutan dengan wilayah lain, khususnya kawasan peri-urban di sekitar Jakarta, dalam mengelola sistem pangan Jakarta.Kata kunci. ketahanan pangan kota, megapolitan, Jakarta